Full-scale Tests of Ground Anchors in Alluvium Soils of Egypt - M. F. Awad-Allah (Lowland Technology International, 2018)
This paper presents full-scale pullout ground anchor tests conducted in some types of alluvial soil formations in Egypt, including silty sand, sandstone, and clay soils. The tests were carried out up to failure loads in order to estimate the ultimate load of friction bearing capacity for each soil stratum. Moreover, an elaborated site investigation program was performed to predict the in-situ soil properties. This research campaign is a part of construction of residential and commercial complex which comprises six underground basements, and the site is located in a vital and highly traffic zone of Heliopolis, Cairo, Egypt. Field test setup and installation method of the full-scale ground anchors were explained. The results of the field tests were compared against the design values of unit skin friction resistance given by the well-known codes of practice (AASHTO; BS 8081; and Canadian Foundation Engineering Manual) and the literature for design of ground anchorage. The comparison showed that the values of skin friction resistance for anchorsoil/rock interface given in AASHTO (2004) and BS 8081 (1989) can be employed for determination of pullout capacities of ground anchors installed in Egyptian soils with a good reliability.